Unveiling Business Startups: A Systematic Literature Review of Challenges and Strategies - Chhayna Cheng (Journal Business Administration: Entrepreneurship and Creative Industry, 2026)
Launching a new business is a complex and dynamic process that requires entrepreneurs to overcome significant challenges through effective strategic responses, promoting sustainability and growth. Prior research has identified various challenges and strategies related to business startups. However, these studies have generally examined challenges and strategies separately, with limited integration of these key aspects into a cohesive framework that spans organizational, regional, and sectoral levels. This study addresses this gap through a systematic literature review by identifying, selecting, synthesizing, and integrating key challenges and strategies of start-ups into a unified model applicable across diverse contexts. Using a systematic review and document analysis guided by inclusion and exclusion criteria and the PRISMA framework, 79 scholarly articles published between 2020 and 2026 were systematically analyzed to generate new insights. The review highlights key challenges, including government policies and regulations, high start-up costs, intense competition, psychological pressures, marketing and customer acquisition, human resource management, and environmental uncertainty. These challenges create complex strategic demands, underscoring the need for effective strategies that help entrepreneurs manage and sustain their businesses. The study also identifies various strategies, including entrepreneurial traits, business planning, technology use, marketing tactics, financial support, research and development, strategic management, ethical practices, networking, and government assistance, which have been employed across different contexts to enhance survival, sustainability, profitability, competitiveness, and long-term success. Overall, the study suggests future research directions to further explore business start-up challenges and strategies across various contexts using comparative and context-sensitive approaches to advance theory and practice.